The Effect of Training Using (Weightlifting- Rubber Ropes) on the Curve of Change in Muscle Ability and (VO2max) and the Ability to Recover and the Accuracy of the Skills of Chest Handling and Shooting to Jump for Young Basketball Players - Hoyt, Mohamed Abdel-Naby Mohamed; Hoyt, Nour Abdel Nabi Mohamed (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed at identifying the extent of identifying the effect of the training methodologies (weightlifting and rubber cords) on the change curve in the development of muscle capacity and (VO2max) and the retrospective ability and accuracy of chest-handling skills and the correction of jumping for young basketball players, and the researchers adopted the experimental research method on a sample of Al-Karkh club players The youth athlete, the number of individuals in the sample reached (12) players, which were divided into two groups so that the first group is trained on weightlifting and the second rubber ropes, for the period from 11/20/2016 until 20/2/2017, and after applying physical, physiological and skill tests under consideration The implementation of the two training programs and the conducting of dimensional tests, the results of which were statistically addressed using the Statistical Bag for Social Sciences (SPSS) version (V24), the researchers concluded that it is possible to reach that the two training methodologies (weightlifting and rubber cords) on the curve of change in the development of muscle capacity and ( VO2max), the ability to recover and the accuracy of the skills of chest handling and shooting to jump for young basketball players in various proportions.